2012
DOI: 10.1097/jom.0b013e318243298c
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Subclinical Atherosclerosis in Firefighters

Abstract: This study supports an emphasis on traditional risk factors for atherosclerotic disease in firefighters, in particular maintaining LDL-C less than 100 mg/dL. Plasma soluble P-selectin may help identify firefighters at increased risk for carotid plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…Results of CIMT meta-analysis strengthen the evidence of early atherosclerotic development in children with FH. Circulating low-density lipoprotein (LDL-C) concentrations were associated with CIMT [ 33 , 34 ], and high levels of oxidized LDL (OxLDL) were significantly associated with progression and increased levels of CIMT [ 35 - 37 ]. Low levels of HDL cholesterol or relative levels of the HDL 3b subclasses and changes in the proportion of small HDL particles were significantly associated with an increased in CIMT [ 20 , 38 ] and with the presence of carotid plaques [ 39 ].…”
Section: The Associations Between Cimt and Traditional CV Risk Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Results of CIMT meta-analysis strengthen the evidence of early atherosclerotic development in children with FH. Circulating low-density lipoprotein (LDL-C) concentrations were associated with CIMT [ 33 , 34 ], and high levels of oxidized LDL (OxLDL) were significantly associated with progression and increased levels of CIMT [ 35 - 37 ]. Low levels of HDL cholesterol or relative levels of the HDL 3b subclasses and changes in the proportion of small HDL particles were significantly associated with an increased in CIMT [ 20 , 38 ] and with the presence of carotid plaques [ 39 ].…”
Section: The Associations Between Cimt and Traditional CV Risk Factormentioning
confidence: 99%
“…Additionally, 12Â months of Mediterranean diet intervention caused a significant reduction in CIMT [ 31 ]. Interventions to lower LDL cholesterol from the suboptimal to the optimal range were shown to have potentially significant benefits to firefighters [ 34 ]. Atorvastatin [ 47 ], rosuvastatin [ 48 ] and fuvastatin [ 49 ] treatments slowed or reduced the progression of CIMT; intensive lipid lowering and antihypertensive therapy along with a reduction in central fat [ 50 ] may be considered a mandatory treatment strategy in young patients with FH to prevent atherosclerosis and to increase arterial stiffness.…”
Section: The Associations Between Cimt and Traditional CV Risk Factormentioning
confidence: 99%
“…In persons with left ventricular ejection fraction >50%, plasma sP-selectin was shown to predict cardiac events [14]. In men at higher risk of cardiovascular disease, sP-selectin associates with the presence of carotid plaque [15]. In non-Hispanic white Americans, over a 10-year follow-up, baseline plasma sP-selectin was related to the future risk of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Varleta et al 38 showed that age, dyslipidemia, systolic blood pressure, and abdominal obesity were predictors of an increase in thickness of the carotid intima-media in a study group of 187 participants. Additionally, Burgess et al 39 reported that LDL levels >100 mg/dl, age, hypertension, and plasma-soluble P-selectin were factors that increased the risk of carotid artery plaques in a study on 597 men. In the present study, no significant difference was found in mean HDL values among the groups.…”
Section: Discussionmentioning
confidence: 99%